Student's Sport as Indicator of Cultural Development of Society - Korbukova, Nelya Alekseevna; Podkopayeva, Evgenia Gennadyevna; LÐ¾ktionova, Svetlana Nikolaevna; Soltan, Natalya Pavlovna; Budnikova, Irina Anatolyevna (International Review of Management and Marketing, 2016)
In this article the authors investigate and reveal the trend and the priorities of the modern students and the choice of an active life position. Sports-mass work with students of the University is seen as a developmental educational, Patriotic and communicative functions of the student. The development of university and mass sport is a vital topic of extreme importance. Now, after several crises in our country, young people are gradually returning to the sport. Various sections which in the basis are urged to increase the level of sports preparation of youth are created. Introducing the all-Russian physical culture-sports complex RLD (ready for labor and defense) that allows organizing sport achievements and scientific knowledge, gives students the opportunity to show a new side of them, to develop new skills. Millions of young people participating in student and public events, improve their physical qualities and motor capabilities, enhance health and prolong creative longevity, and thus resist unwanted influences on the organism of modern production and the conditions of daily life. University sport plays a very important role in the preparation of viable and socially active young generation, shaping the culture of youth. It acts as building block in the formation of the culture of the society. Since the young generation is a very important socio-structural component and in the future it will emerge as a society need at an early age stages to generate in people a culture of behavior, communication, social relationships. Keywords: student's sport, mass sport, health, way of life. JEL Classifications: Z200, Z280, I180